Gurus and Media Sound, image, machine, text and the digital - Copeman, Jacob; Longkumer, Arkotong; Duggal, Koonal (UCL Press, 2023)
Gurus and Media is the first book dedicated to media and mediation in domains of public guruship and devotion. Illuminating the mediatisation of guruship and the guru-isation of media, it bridges the gap between scholarship on gurus and the disciplines of media and visual culture studies. It investigates guru iconographies in and across various time periods and also the distinctive ways in which diverse gurus engage with and inhabit different forms of media: statuary, games, print publications, photographs, portraiture, films, machines, social media, bodies, words, graffiti, dolls, sound, verse, tombs and more. The book's interdisciplinary chapters advance, both conceptually and ethnographically, our understanding of the function of media in the dramatic production of guruship, and reflect on the corporate branding of gurus and on mediated guruship as a series of aesthetic traps for the captivation of devotees and others. They show how different media can further enliven the complex plurality of guruship, for instance in instantiating notions of 'absent-present' guruship and demonstrating the mutual mediation of gurus, caste and Hindutva. Throughout, the book foregrounds contested visions of the guru in the development of devotional publics and pluriform guruship across time and space. Thinking through the guru's many media entanglements in a single place, the book contributes new insights to the study of South Asian religions and to the study of mediation more broadly. Praise for Gurus and Media 'Sight, sound, image, narrative, representation and performance in the complex world of gurus are richly illuminated and deeply theorised in this outstanding volume. The immensely important, but hitherto under-explored, visual and aural dimensions of guru-ship across several religious traditions have received path-breaking and wide-ranging treatment by best-known experts on the subject.' Nandini Gooptu, University of Oxford 'Gurus and Media casts subtle light on a phenomenon that too often shines so brightly that it is hard to see. This collection is a tremendously rich resource for anyone trying to make sense of that ambiguous zone where authority appears at once as seduction and as salvation, as comfort and as terror.' William Mazzarella, University of Chicago 'This remarkable collection uses the figure of the mass-mediated guru to throw light on how modern Hindu mobilization generates a highly diverse set of religious charismatics in India. Because of the diversity of the contributors to this volume, the book is also a moveable feast of cases, methods and cultural styles in a major cultural region.' Arjun Appadurai, Emeritus Professor of Media, Culture and Communication, New York University